Language Learning Strategies (LLS): Teachers’ Notions and Practice - Kussin, Haddi Junaidi; Omar, Ainon; Kepol, Napisah (Dinamika Ilmu: Jurnal Pendidikan, 2018)
The purpose of the study was to find out both notions and practice where LLS are concern. The study targeted the teacher population at Centre for Foundation Studies of the International Islamic University Malaysia, particularly teachers responsible of teaching English at the educational institution. However, there were only four teachers who responded to the invitation to become part of the study. The study first explored the individual perception of the four teachers who volunteered (done via three separate interview sessions) before lesson implementations of the four were observed to substantiate their notions on incorporating LLS into lesson implementations. The notions of the four volunteered teachers were found to have aligned with their individual practices where LLS are concern.